BOOK REVIEW. FIRST OF BANYAN TREES - Henny Indarwaty (Humaniora, 2015)
The ever fascinating part of an anthology is found in its diverse writings, in both the theme and style. That is also true to Rayuan Pohon Beringin (Flirt of banyan tree), an anthology of short stories published by Gadjah Mada University Press. The anthology is a collection of short stories in the Literature and Arts Award I, held for the first time by the Faculty of Cultural Sciences UGM. The title is taken from one of the winners of the short story competition – “Rayuan Pohon Beringin” (Flirt of banyan tree).